PENERAPAN BUDAYA PAMALI DAN ADAT ISTIADAT DALAM KEHIDUPAN MASYARAKAT KAMPUNG ADAT KUTA KABUPATEN CIAMIS JAWA BARAT - SRI DWI FAJARINI; DHANURSETO DHANURSETO (Professional: Jurnal Komunikasi dan Administrasi Publik, 2019)
Indonesia has nations and culture scattered around 17,000 ranges island, starting from sabang to the west, to marauke to the east irian jaya.Life the people in indonesia has the pattern formed based on the influence of local culture place they live.This means culture and style community life in indonesia varies.One of the influential in the life of people will examined is a culture and the community mores their kuta, kabupaten ciamis, west java. Their customary kuta shows a pattern spread out and did not feel certain .This research aims to review the application of local cultural factors in the life of the indigenous people of kampung kuta . The methodology that was used is mixed methods , with a design research used in this research was sequential exploratory designs .The data collection was done by interviews , observation and spreading kampung kuta watchful such research to the community. Results or research is the their kuta always apply cultural factors and customstheir kuta in her life, starting with the smallest to great things though because people would hold fast in culture pamali. Keyword : culture, kuta village, the life of the people